2013
DOI: 10.1186/2046-4053-2-107
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bias: a simulation study of power to detect study-level moderator effects in meta-analysis

Abstract: BackgroundThere are both theoretical and empirical reasons to believe that design and execution factors are associated with bias in controlled trials. Statistically significant moderator effects, such as the effect of trial quality on treatment effect sizes, are rarely detected in individual meta-analyses, and evidence from meta-epidemiological datasets is inconsistent. The reasons for the disconnect between theory and empirical observation are unclear. The study objective was to explore the power to detect st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 30 publications
0
96
1
Order By: Relevance
“…This is likely to be an issue in the current meta-analyses, as the samples included contain 10 or fewer studies. This possibility is supported by a recent review which simulated the power of moderator analyses given the number of studies in a meta-analysis, the number of participants in these studies and the expected moderator effect size 25. With reference to their findings, a meta-analysis of the current study's size may not have sufficient power (0.8) to reliably detect a small-to-medium moderator effect.…”
Section: Discussionmentioning
confidence: 96%
“…This is likely to be an issue in the current meta-analyses, as the samples included contain 10 or fewer studies. This possibility is supported by a recent review which simulated the power of moderator analyses given the number of studies in a meta-analysis, the number of participants in these studies and the expected moderator effect size 25. With reference to their findings, a meta-analysis of the current study's size may not have sufficient power (0.8) to reliably detect a small-to-medium moderator effect.…”
Section: Discussionmentioning
confidence: 96%
“…A sufficient sample was defined as having at least three studies in a category, or a minimum sample size of 250 participants per category. A sample size smaller than this was shown not to have sufficient power to detect even large, homogeneous moderator effects [46]. This minimum sample size was thus chosen to make meaningful moderator analyses, without being overly restrictive.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted, however, that the statistical power of moderator analyses in meta-analysis is not always high 40 and that a large number of studies is generally needed to detect effects. 41 Given that research about active videogames is still in its infancy, so that not many published studies exist, 9,16 the results of these analyses should be considered with caution. No moderator analyses were performed in case of limited heterogeneity.…”
Section: Effectiveness Of Active Videogamesmentioning
confidence: 99%
“…32 In addition, moderator analyses have only limited power with a small set of studies. 40,41 This latter limitation is particularly noteworthy given the substantial heterogeneity that was found in the elderly studies. Our results revealed that 68 percent of the variance in effect sizes across the elderly studies was attributable to systematic differences.…”
Section: Effectiveness Of Active Videogamesmentioning
confidence: 99%
See 1 more Smart Citation